Electrical and optical properties of ZnO-Fe2O3-SiO2 composite prepared by SOL-GEL method - Canbay, C. Aksu; Altin, S.; Aydogdu, A.; Aydogdu, Y.; Yakinci, E. (Amer Inst Physics, 2007)
The semiconductor composite was prepared from ZnO, Fe2O3 and SiO2 transition metal oxides by sol-gel method. The surface morphology of the prepared samples were investigated by scanning electron microscopy (SEM). The activation energies of the samples in the extrinsic and intrinsic regions were found as 0.75 eV and 0.77 eV for ZFS-1 and 0.22 eV and 0.32eV for ZFS-2. The value of the optical band gap of the composite samples were calculated from the absorption coefficient depending on photon energy. The optical band gap of the samples were found as 1.60 eV and 1.70 eV for ZFS-1 and ZFS-2, respectively.
6th International Conference of the Balkan-Physical-Union -- AUG 22-26, 2006 -- Istanbul, TURKEY
Keywords: composite; transition metal oxides; activation energy; semiconductor